Theoretical Implications of Renewable Energy using Improved Cooking Stoves for Rural Households - Ul Haq, Muhammad Abrar; Nawaz, Muhammad Atif; Akram, Farheen; Natarajan, Vinodh K. (International Journal of Energy Economics and Policy, 2020)
Majority of the rural people from developing countries are dependent on agriculture sector and the major source of energy is traditional biomass. Due to radical climate changes, their dependency on traditional biomass and agriculture sector increases their vulnerability and deteriorates the environment as well. Therefore, this study attempts to highlight the potential of using renewable energy options to reduce this vulnerability. The focus of present research is the efficient utilization of solar energy and biomass using improved cooking stoves. Additionally, the vulnerability can be reduced by optimizing solar energy utilization and enhanced individuals’ adaptive capacity with the use of improved cooking stoves. The environmental benefits of the use of improved cooking stoves through solar energy are also discussed. It is concluded that the efficient use of biomass and solar energy reduce individuals’ susceptibility and improve their socio-economic status, education, health and climate change as well. These findings provide the guidelines to the regulators that they should enhance their focus towards renewable energy to reduce this vulnerability. Keywords: Health Benefits, Solar Energy, Renewable Energy, Biomass. Climate Change JEL Classifications: Q26; Q54 DOI: https://doi.org/10.32479/ijeep.10216